Unintended pregnancies, induced abortions and risk factors in women admitted to hospitals due to birth or abortion in Hatay - Nazan Savaş; Tacettin İnandı; Evrim Arslan; Ersin Peker; Elif Durmaz; Mehmet Erdem; Ömer Alışkın; Arif Yeniçeri (Turkish Society of Public Health Specialists, 2017)
Objective: The aim of this study is to determine the frequency of unintended pregnancies, induced abortions and associated risk factors in women who have been admitted to hospitals in Hatay. Method: The subjects of this cross-sectional study were women who had been admitted to hospitals for the purposes of delivery or abortion, during a month-long period. A structured questionnaire was taken by 635 women. Unintended pregnancy was dependent variable. The independent variables were: age, husband's age, civil status, total number of pregnancies, employment, use of family planning methods and family planning consultation services. Chi-square and Student's t-test were used to analyze of data. Results:21.4% of women reported using a family planning method when they got pregnant and 15.1% of the women said they did not want to be this pregnant. Ages of the women and their husbands, as well as the total number of pregnancies, were higher among unintended pregnancies (p<0.05). The frequency of unintended pregnancies increased where the husbands were unemployed, education levels of the couple were low, women were single or not officially married, disabled, or did not receive consultancy from their family physicians about family planning (p<0.05). 45.8% of all unintended pregnancies happened without the use of any family planning methods (p<0.01). 10.4% ended with spontaneous abortions and 4.25% were ended with induced abortions. The primary reason given for induced abortion was economic difficulties (44%). Conclusion: Unintended pregnancy rate is high in Hatay. It is estimated that almost half of all induced abortions are reported as spontaneous or therapeutic abortions.